2013
DOI: 10.4067/s0718-58392013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for fresh consumption of new broad bean genotypes with a determinate growth habit in central Chile

Abstract: Broad bean (Vicia faba L. [unranked] major (Harz) Beck) is usually consumed dry. In Chile, however, broad bean is grown as a vegetable crop with indeterminate genotypes. The new 'Alargá', 'Retaca' and 'Verde Bonita' broad bean genotypes, which have a determinate growth habit, were evaluated in six irrigated environments in central Chile at three locations (Rancagua, Talca, and Talagante) and on two planting dates (F1 and F2; 1-mo apart). The aim was to characterize their yield and select the best-yielding gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
7
0
5
Order By: Relevance
“…These values are higher than the state average of Mexico, which is 6 t ha -1 and are located within the range recorded by Baginsky et al (2013) of 7. 6.…”
Section: Conclusionessupporting
confidence: 62%
See 1 more Smart Citation
“…These values are higher than the state average of Mexico, which is 6 t ha -1 and are located within the range recorded by Baginsky et al (2013) of 7. 6.…”
Section: Conclusionessupporting
confidence: 62%
“…El cultivar 32 (12.83 t ha -1 ), denominado San Pedro Tlaltizapán, fue superior en rendimiento en verde (RV), seguido de 1, 6, 20, 31, 2, 4, 7, 8 y 35 entre 11.15 y 12.42 t ha -1 ; (Cuadro 5, Figura 1). Estos valores son mayores a la media del estado de México, que es de 6 t ha -1 , y se localizan en el intervalo registrado por Baginsky et al (2013), de 7. 6 a 15.…”
Section: Resultsunclassified
“…weight (Baginsky et al, 2013). The colonization rate (% COL) was also correlated with root length (LRz), arbuscules percentages (% ARB), hyphae (% HIF), vesicles (% VES) and pink nodules (NDRs).…”
Section: Conclusionesmentioning
confidence: 99%
“…Overall the immature pods yields were a 25.8% (on average) lower than those reported in the literature, which are between 0.39 and 1.55 kg m −2 . 30,31 The differences between the two faba bean genotypes ('VF_001' and 'VF_002'), concerning the immature pods and mature seeds yield in 2014 and 2015, revealed that 'VF_001' is better adapted to the changing climatic conditions than 'VF_002', which must be taken into consideration when selecting the cultivar according to the agro-environmental conditions of the geographical area (northern Europe).…”
Section: Influence Of Vegetable Crops On Faba Bean Yield In the Full mentioning
confidence: 99%
“…This fact could be due to the shallow root system characteristic of onions, which competes (with a disadvantage) with the dense root system of faba bean for water and nutrients. Since almost 65% of the faba bean root system is located at a depth of 0.15 m, 30 and its water demand is high, 9 the competing ability of faba bean is quite strong for onion. 35 The sensitiveness of onion to water deficiency has been already reported by Kalbartcyk et al, under Polish agro-climatic conditions, which supports the relatively low yield of onions in faba bean intercropping.…”
Section: Influence Of Faba Bean On Vegetables Yield In the Full Intermentioning
confidence: 99%